The Effect of Sensory Kinetic Exercises in the Development of Some of the Functional Abilities and the Accuracy and Strength of Serving Skill in Tennis - Hameed Hammad Khalaf (Journal of Global Pharma Technology, 2018)
The problem lies in the apparent decrease in the accuracy and strength of the serving performance of theAnbar University team in tennis and the lack of focus on the mental abilities and linking them to thephysical and skillful aspects, which necessitated the researchers to go into this problem through thedevelopment of sensory - kinetic exercises to address this decline. The research aims at identifying theeffect of sensory-kinetic exercises in the development of the functional abilities, and the accuracy andstrength of serving in tennis. The researchers hypothesized that the impact of exercises has a statisticalsignificance on the functional abilities and the accuracy and strength of the skill of serving in tennis.They used the experimental approach to design the two equal groups and on a sample of (12) players.The field procedures of the research were by conducting the pretests on Wednesday, 4/10/2017 at 11amon the outdoor tennis court and the closed hall at the college. The sensory-kinetic exercises were carriedout over 6 weeks at three units per week. On Sunday, 12/11/2017 at 11 am the post-tests were conductedin the same court and conditions similar to the conducting of the pretests. The researchers concludedthat the controlling and experimental groups developed but the experimental group that used sensorykineticexercises was more advanced in the post-tests. They recommend the emphasis on using thesensory-kinetic exercises to develop the skill of serving, other tennis skills, and other individual andteam sports.Keywords: Sensory, Kinetic exercises, Functional abilities, Accuracy and Serving skill.